Type II NKT Cell Agonist, Sulfatide, Is an Effective Adjuvant for Oral Heat-Killed Cholera Vaccines - Aqel Albutti; Stephanie Longet; Craig P. McEntee; Shauna Quinn; Alex Liddicoat; Cristiana Rîmniceanu; Nils Lycke; Lydia Lynch; Susanna Cardell; Ed C. Lavelle (Vaccines, 2021)
Oral vaccination has the potential to offer a safer and more efficacious approach for protection against enteric pathogens than injection-based approaches, especially in developing countries. One key advantage is the potential to induce intestinal immune responses in addition to systemic immunity. In general, antigen delivery via the oral route triggers weak immune responses or immunological tolerance. The effectiveness of oral vaccination can be improved by co-administering adjuvants. However, a major challenge is the absence of potent and safe oral adjuvants for clinical application. Here, the Type II NKT cell activator sulfatide is shown for the first time to be an effective oral adjuvant for Vibrio cholerae vaccine antigens in a mouse model. Specifically, administration of sulfatide with the oral cholera vaccine Dukoral® resulted in enhancement of intestinal antigen-specific IgA in addition to Th1 and Th17 immune responses. In summary, sulfatide is a promising adjuvant for inclusion in an oral cholera vaccine and our data further support the potential of adjuvants targeting NKT cells in new vaccine strategies.